1990
DOI: 10.1002/hep.1840110221
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Steroids As A Risk Factor for Hepatocellular Carcinoma: A Case/Control Study in South African Black Women

Abstract: The role of contraceptive steroids in the etiology or pathogenesis of hepatocellular carcinoma in urban South African black women was investigated in a hospital-based case and control study. Participating were 46 women, 19 to 54 yr old, with carcinoma, and 92 matched controls. South African blacks have a high incidence of hepatocellular carcinoma, and urban black women have used contraceptive steroids fairly widely for a number of years. Use of contraceptive steroids for longer than 6 mo (mean duration 46.7 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…In fact, 2 studies involving a larger number of cases that included women in regions endemic for HBV infection and HCC found a statistically nonsignificant decreased risk of HCC for use of oral contraceptives. 26,27 The effect of exogenous estrogen use on the reduction in HCC risk observed in this study is consistent with the Compared with never-users, P trend ϭ .0013 for ever-users with duration of use Յ12, Ͼ12 and Յ36, and Ͼ36 months. ¶Compared with never-users, P trend ϭ .0060 for ever-users with duration of use Յ12, Ͼ12 and Յ36, and Ͼ36 months.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, 2 studies involving a larger number of cases that included women in regions endemic for HBV infection and HCC found a statistically nonsignificant decreased risk of HCC for use of oral contraceptives. 26,27 The effect of exogenous estrogen use on the reduction in HCC risk observed in this study is consistent with the Compared with never-users, P trend ϭ .0013 for ever-users with duration of use Յ12, Ͼ12 and Յ36, and Ͼ36 months. ¶Compared with never-users, P trend ϭ .0060 for ever-users with duration of use Յ12, Ͼ12 and Յ36, and Ͼ36 months.…”
Section: Discussionsupporting
confidence: 87%
“…Several case reports have described the occurrence of liver adenomas or focal nodular hyperplasia in women taking oral contraceptives, 20 and the possible association between use of oral contraceptives and the risk of HCC has been assessed in several studies. 3,17,[21][22][23][24][25][26][27] However, most of these studies were based on a very limited number of case subjects, and the results have been incon- …”
mentioning
confidence: 99%
“…However, in populations with high prevalence of hepatitis virus infection, no significant relationship was found (WHO, 1989;Kew et al, 1990). A recent metaanalysis of 12 case-control studies indicated no association between short term OC use and risk of HCC, but the author did mention the possibility of a causal relationship in non-hepatitis B endemic areas with long-term OC use (Maheshwari et al, 2007).…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…Several studies, generally using small sample sizes, investigated a possible link between OC and HCC. The findings of these studies have been inconsistent and either included an increased risk of HCC [14,16,17,22] or no association [11][12][13]15,[18][19][20][21]. Therefore, we conducted this review and meta-analysis to critically examine the epidemiological evidence for the association between OC use and HCC risk.…”
Section: Introductionmentioning
confidence: 98%